Uma abordagem etnomatemática sobre as implicações dos números no Batuque do Rio Grande do Sul - Vargas, Jackson Luís Santos de (2016)
The study presents an analysis of the generation´s, organization´s and diffusion´s process, related to knowledge about the relation of numbers and mystic representation, used in Batuque from Rio Grande do Sul. The participants that participate of the survey were four babalorixás with more of 20 years of cult to the orixás and they belong to some nações that are practed in Rio Grande do Sul. All the participants live in Rio Grande do Sul and it´s ilês are operating.The instruments used to collect information were an interview from a semi structures questionary and with observations realized at one of the babalorixá´s Ilê. The method used was Etnomathematics present on the researchs of D´Ambrósio (1985,1993,1996, 2001) and Gerdes (1989,1991,2012). To analyze the answers given by the participants of the survey, was used discursive textual analyses ( MORAES; GALIAZZI, 2011). First the categories were structures in three types : knowledges´s generation; knowledge´s organization and knowledge´s diffusion. Using this categories, new categories were created making possible the understanding of the answers for the questions of the survey. Using the conventions realized by the precorsors of Batuque in Rio Grande do Sul, it´s evident that in relation of the generation of knowledge each Orixá has a number, multiple and submultiple related, and this number must be respect in all the obligations. The knowledge´s organizations shows that exist defined rules about the use of numbers which are sacred. In relation to that , the belief in geometric shapes is required to preserv the cult and it´s organization.The knowledge´s diffusion shows that numbers are used in all the rituals that belongs to Batuque of Rio Grande do Sul, because they represent the orixás. Besides, the analysi´s results reveal that numbers used are essencial for the maintenance and to continue the cult using the numbers multiples and submultiples of each Orixá that are organized all the rituals of Batuque from Rio Grande do Sul. Since an simple offering until monetary values that are collected on the ilês, the numbers of the orixás are involved and are representative. The using of geometry to prepare the food for the orixás also obey rules related to the Nação that is praticed. I conclude that although the participants don´t know exactly how to explain the origin of the numbers, inside of the culture, the analyze about what they said shows that it was associated by the miths that each Orixá has, and for the mystic meaning that numbers represents for the african culture.